1997
DOI: 10.1128/jvi.71.3.1897-1905.1997
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recombinant adeno-associated virus packaging and requirements for rep and cap gene products

Abstract: Adeno-associated virus (AAV) is a human parvovirus currently being developed as a vector for gene therapy applications. Because the gene transfer vector commonly retains only the AAV terminal repeats, propagation of recombinant AAV (rAAV) requires that the viral replication (Rep) and capsid (Cap) proteins be supplied in trans. In an effort to optimize the production of these vectors, a panel of helper plasmids was constructed to determine if expression of the rep and/or cap genes is a limiting factor for rAAV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 59 publications
4
31
0
1
Order By: Relevance
“…These results suggest that sufficient expression of capsid protein is important for AAV vector production and that a large amount of Rep78/68 and/or reduced amount of Rep52/40 have deleterious effects on AAV vector production. These findings are compatible with recent reports (20,37). Recent studies also showed that overexpression of Rep78/68 inhibits Cap expression, but the effect on Rep52/40 expression was unclear (20,37).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that sufficient expression of capsid protein is important for AAV vector production and that a large amount of Rep78/68 and/or reduced amount of Rep52/40 have deleterious effects on AAV vector production. These findings are compatible with recent reports (20,37). Recent studies also showed that overexpression of Rep78/68 inhibits Cap expression, but the effect on Rep52/40 expression was unclear (20,37).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we investigated the relation between Rep expression patterns and the efficiency of AAV vector production by adjusting differences in the amount of Cap from various helper plasmids. The production of capsid proteins is one limiting factor for rAAV packaging and overexpression of Rep78/68 inhibits rAAV DNA replication and cap gene expression, resulting in the reduction of rAAV titer (20,37). These previous findings were confirmed by this study, and we found that overexpression of Rep78/68 inhibited not only Cap expression but also Rep52/40 expression in the presence of adenoviruses.…”
supporting
confidence: 87%
“…A previous report showed that the production of capsid proteins is a limiting factor for packaging the AAV vector genome and that overexpression of Rep78/68 leads to a much reduced AAV vector titer. 31) On the other hand, down regulation of Rep78/68 expression by using an inefficient translation initiation start signal caused increased capsid protein expression, resulting in much higher AAV vector yields. 32) Thus, our findings are compatible with these earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…This is usually done by removal of all viral genes between the 5 Ј and 3 Ј terminal repeat (TR) sequences and replacing them with the desired transgene(s) ( Dong et al, 1996 ). Since the only viral DNA sequences the rAAV vectors retain are the TRs, the vectors must be propagated in a special packaging cell lines that express the AAV Rep and Cap proteins, in addition to the helper virus co-infection ( Vincent et al, 1997 ). This has both advantages and disadvantages.…”
Section: Adeno-associated Virusmentioning
confidence: 99%